The Free Economy and the Strong State - Gamble, Andrew. author. aut Link
XII, 263 p.
Keywords: An attempt to provide an account of the genesis of Thatcherism in opposition, its record in government, its relationship to the Conservative tradition and the ideological challenge of the New Right. The manner in which Thatcherism has been analysed by the Left and the Right is assessed.